Universally Designing in Universal Chaos. - Tucker, Lauren (Remote Teaching and Learning: Reflections and Practical Advice, 2021)
Looking back on a year of tumultuous teaching and learning amid restrictions set in place after the COVID-19 pandemic began in early 2020, Remote Teaching and Learning: Reflections and Practical Advice focuses not only on the trials and tribulations higher ed faculty have endured but also the insights learned, silver linings revealed, and successes achieved through emergency remote teaching. Hear from 20 educators whose contributions include: reflections on pandemic teaching; strategies and practical advice; and resources for students.Whether you’re returning to a face-to-face classroom, continuing to teach online, or exploring hybrid or HyFlex teaching, you’ll find wisdom, advice, and observations from educators with a shared commitment to student learning. Includes student handouts to use in your classroom!
Keywords: dept.sed